PELUANG BISNIS PADA PENERAPAN INDUSTRIAL INTERNET OF THING (IIoT) - Achmad Solechan; Jarot Dian Susatyono; Toni Wijanarko AP.; Febryantahanuji Febryantahanuji (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2022)
This research was conducted using qualitative methods and exploratory literature review, where after a number of journal references were collected, a theoretical study, research results and discussion of this literature review article were carried out in the Industrial Internet of Things (IIoT) concentration. This research presents the results of a study of business opportunities from the use of the Industrial Internet of Things (IIoT). IoT can be implemented in various fields of the modern economy, for example: health, environment, defence, quality control, transportation, logistics, clean water, building / construction, industrial production / manufacturing, energy sources, agriculture and plantations. By utilizing IIoT, companies can benefit from technology investments made from saving operational costs and increasing company revenue. The suggestions for this research include the need to develop the implementation of IIoT in various fields so that it is more effective, efficient and provides convenience to companies. Future research needs to analyze opportunities, challenges and directions for future research work related to IIoT regarding the benefits of using IIoT technology including real-time, coexistence, interoperability, optimal security and privacy.